2017
DOI: 10.4103/1793-5482.180972
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations of intracranial aneurysm formation and sub-arachnoid hemorrhage

Abstract: Risk factors for cerebral aneurysms typically include age, hypertension, smoking, and alcohol usage. However, the possible connection of aneurysms with genetic conditions such as Marfan's syndrome, polycystic kidney disease, and neurofibromatosis raises the question of possible genetic risk factors for aneurysm, and additionally, genetic risk factors for rupture. We conducted a literature review using the PubMed database for studies regarding genetic correlation with cerebral aneurysm formation as well as rupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…A disrupted balance between ECM synthesis and degradation may be the pathophysiological basis for IA formation ( 13 , 14 ). For example, some single nucleotide polymorphisms (SNPs) of endothelin receptor type A ( EDNRA ), alpha 1 type III collagen ( COL3A1 ), transcription factor SOX-17 ( SOX17 ), and lysyl oxidase-like 2 ( LOXL2 ), which are mainly involved in ECM reconstruction, are associated with IA ( 15 18 ). The LOXL2 gene belongs to the lysyl oxidase (LOX) family that comprises LOX and lysyl oxidase-like 1–4 ( LOXL1 , LOXL2 , LOXL3 , and LOXL4 ) ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…A disrupted balance between ECM synthesis and degradation may be the pathophysiological basis for IA formation ( 13 , 14 ). For example, some single nucleotide polymorphisms (SNPs) of endothelin receptor type A ( EDNRA ), alpha 1 type III collagen ( COL3A1 ), transcription factor SOX-17 ( SOX17 ), and lysyl oxidase-like 2 ( LOXL2 ), which are mainly involved in ECM reconstruction, are associated with IA ( 15 18 ). The LOXL2 gene belongs to the lysyl oxidase (LOX) family that comprises LOX and lysyl oxidase-like 1–4 ( LOXL1 , LOXL2 , LOXL3 , and LOXL4 ) ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among nine eligible studies, four studies were excluded from the final analysis because they lacked the outcomes of interest [18] or were meta-analyses [10] or review studies [8,19]. Finally, a total of seven independent cohort studies in five articles were selected for the meta-analysis: Two European GWASs including Finnish and Dutch populations [20]; two Japanese GWASs [5,20]; one European-ancestry candidate gene study including populations from North America, New Zealand, and Australia [21]; one Japanese candidate gene study [22]; and one Korean GWAS (Figure 1) [11].…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35] A systematic literature review showed that the 9p21/CDKN2, a loci which is implicated in vessel wall remodeling, had the strongest association with aneurysm rupture (Odds ratio: 1.42; p=0.01). 36 Another large scale genome-wide association study with approximately 2,000 patients with CAs and 8,000 controls reported single nucleotide polymorphisms in the 2q33.1, 8q11.23 and 9p21.3 loci, which are thought to be associated with sporadic and familial CAs. 37 Candidate genes that have been studied are MMPs, angiotensin-converting enzyme, phospholipase C, NOS, transforming growth factor-beta receptor among others.…”
Section: Ii) Geneticsmentioning
confidence: 99%